STRATEGI MENDOMINASI BENAK KONSUMEN DAN PASAR MELALUI STV (STRATEGI - TAKTIK - VALUE) TRIANGLE (Studi Pada Industri Minuman Energi Di Indonesia) - David Sukardi Kodrat (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2006)
The business development is driven by information system and digitalization, globalization and futurization. The fast growing of information system make consumers are faced by many informations of brand.The purposes of this research are what factors are making to exist a brand for consumers mind dominating and market dominating and how.) is Kratingdaeng strategy for consumers mind dominating and market dominating in energy drink industries.The result of this research show that: (1) all brand try to get place in the mind of consumers. Only the brand that have the right positioning is having a special place in the consumers mind. Positioning have supported by differentiation. Interaction between positioning and differentiation will be created a strong brand. All of those are dominating consumers mind and for dominating market through it's strong marketing mix as product, price, place and promotion and (2)Kratingdaeng changes perception of market from medical to energy drink by educating the market. In educating the market, Kratingdaeng uses TV program especially sport program so brand value Kratingdaeng increase 10.4%' from 304.2 (2005) to be 315.4 (2006) and gam index 21.3. Kratingdaeng is not compete in packaging or pricing hut to give satisfaction to customers (Kratingdaeng has receipt ICSA since 1999) and distribute to all outlet and all area by PT. Arta Boga Cemerlang.